Home country bias in international emissions trading: Evidence from the EU ETS - Beat Hintermann; Markus Ludwig (University of Basel, Center of Business and Economics (WWZ), 2022)
We examine the pattern of allowance trades in the European Union Emissions Trading System (EU ETS) using highly disaggregated trading data and identify a significant and robust home market bias. Our results point to informational transactions costs that increase when trading across national borders. The existing trade pattern in goods and services explains two thirds of the home bias, with the remainder due to other causes. Our finding suggests that firms make use of existing trade networks to overcome search costs in bilateral allowance trade. Since the home bias differs across firms, it follows that marginal abatement costs are not equalized across market participants of the EU ETS.
Keywords: F14; F18; Q52; Q54; Q58; 330; Emission permit market; EU ETS; transactions costs; gravity model; home bias